"Small houses": disruptions or re-ordering sexuality in Zimbabwe? - Hungwe, Chipo (Africa Resource Center, 2016)
The article analyses the Zimbabwean phenomenon of small houses in order to determine whether or not involvement in such sexual arrangements liberate women. It analyses the level of subversion or disruption to sexual power caused by these relationships, and it documents the challenges these women encounter. In the course of the examination, it illuminates the reasons women opt for this type of relationship as well as the peculiar issues of ambivalence, conflicts, frustration, and agency they face within them. By raising questions about agency for small houses, the study simultaneously raises questions about attitudes towards sexuality and sexual desires that are held by small houses, visiting married men, and wives.